Оцінки собівартості та можливих обсягів виробництва електроенергії сонячними електростанціями в Україні - Denysov V.A.; Ivanenko; Chuprina L.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2012)
Given the climate information on the distribution of solar insolation on the territory of Ukraine and the available technological base of photovoltaic power generation, the preliminary estimates of the efficiency of the construction of photovoltaic power plants in the regions of Ukraine are presented. These estimates can be used as a background information to predict the appropriate volumes of the introduction of technologies based on the use of renewable energy sources.